Price formation in a sequential selling mechanism - Radosveta Ivanova-Stenzel; Sabine Kröger (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2005)
This paper analyzes the trade of an indivisible good within a two-stage mechanism, where a seller first negotiates with one potential buyer about the price of the good. If the negotiation fails to produce a sale, a second 'price sealed' bid auction with an additional buyer is conducted. The theoretical model predicts that with risk neutral agents all sales take place in the auction rendering the negotiation prior to the auction obsolete. An experimental test of the model provides evidence that average prices and profits are quite precisely predicted by the theoretical benchmark. However, a significant large amount of sales occurs already during the negotiation stage. We show that risk preferences can theoretically account for the existence of sales during the negotiation stage, improve the fit for buyers' behavior, but is not sufficient to explain sellers' decisions. We discuss other behavioral explanations that could account for the observed deviations.
urn:nbn:de:bvb:19-epub-13459-2
Keywords: C72; C91; D44; D82; 330; auction; negotiation; combined mechanism; sequential mechanism; risk preferences; experiment